Identification and characterization of the elusive protein backbone of the immuno-dominant and species-specific Em2(G11) metacestode antigen of Echinococcus multilocularis - Kronenberg, Philipp A.; Laurimäe, Teivi; Reinehr, Michael; Deibel, Ansgar; Hasler, Sina; Gehrig, Peter; Weber, Achim; Deplazes, Peter; Eichenberger, Ramon M. (Frontiers in Parasitology, 2025)
Alveolar echinococcosis (AE) caused by Echinococcus multilocularis, is a severe zoonotic disease in humans. One of the major metacestode antigens of E. multilocularis is the Em2 or Em2(G11) native purified antigen. The Em2 antigen is used for the serological and histopathological diagnosis of AE in humans and plays an important role in parasite–host interactions. As the Em2(G11) antigen is a mucin-type and glycosylated protein, the protein backbone has not been identified yet. We have targeted the protein backbone identification through mass spectrometry (LC-MS/MS) analysis of the Em2(G11) antigen. As a result, we evidenced that the Em2(G11) antigen consists of 33 unique protein candidates of which the most abundant was ‘’EmuJ_001105600.1’’. This protein (889 amino acids) had 427 predicted glycosylation sites. Amino acid composition comparison was in agreement with earlier studies and further confirmed the candidate of interest as the most likely Em2(G11) protein backbone. NCBI BLAST revealed no other known protein homologues in related Echinococcus species nor helminths. After successfully producing this protein recombinantly (Em2rec), a monoclonal antibody (mAbEm2rec) was raised against it. Immunohistochemical stainings of liver tissue sections of AE patients showed that the mAbEm2rec reacts specifically with E. multilocularis antigens solely after deglycosylation with an O-glycosidase cocktail. Similarly, in ELISA, the mAbEm2rec recognized the recombinant and native antigens of E. multilocularis after deglycosylation. These results reveal the nature of this highly glycosylated and specific protein, where mucins are covering the proteomic backbone. For antibody detection in human patients, the native Em2(G11) antigen was superior compared to the Em2rec antigen, indicating the importance of glycosylated epitopes in this immuno-dominant antigen. Of note is the second most abundant protein in the Em2(G11) antigen, namely phosphoenolpyruvate carboxykinase (PEPCK; EmuJ_000292700.1). PEPCK is known to play an important part in the metabolic pathway of gluconeogenesis in E. multilocularis. However, whether this co-eluted protein has any functional importance in the parasite-host interplay of nutrients, growth, and diagnostic significance, is not explored. By combining various approaches, we were able to uncover and confirm the protein backbone of the diagnostic Em2(G11) antigen of E. multilocularis.